Sharing infrastructure, how to proceed - Alain Maton (International Telecommunications Society (ITS), 2016)
NGA investments request several forms of infrastructure sharing due to the high level of investments, their efficiency vary dramatically following circumstances and areas. The right choice is a key feature to facilitate infrastructure competition. The purpose of the paper is to compare the different available architectures.
Keywords: 330; electronic communications; access regulation; infrastructure sharing; NGA